Some Variants Current Mode Filter via Commercial Integrated Circuits and its Proprieties - Brtník, Bohumil (IEEE (Institute of Electrical and Electronics Engineers), 2023)
The current mode signal processing is useful technique for frequency filters. As is best known, some biquad structures are characterized by a degradation of the attenuation at high frequencies. Loss of attenuation is one proprieties Sallen-Key low-pass filter not only in voltage, but in current mode, as well. Some possibilities to solve this disadvantage are described in this paper.
Některé varianty filtrů v proudovém módu s komerčními integrovanými obvody a jejich vlastnosti
Keywords: current conveyor; transimpedance amplifier; current-mode network; current mode filter; proudový dopravník; transimpedanční zesilovač; síť v aktuálním režimu; Filtr aktuálního režimu